Potential Role of TNFα Gene Expression and TNFα / TNFR1 Levels in the Pathogenesis of Hashimoto’s Thyroiditis in Iraqi Women - Mohamed, Kalaweesh Ali; Abbas, Sahla Khorsheed (Iraqi Journal of Science, 2026)
Tumor necrosis factor alpha (TNF-α) is a pro-inflammatory cytokine that promotes inflammation and the development of some autoimmune diseases (AIDs), including Hashimoto’s thyroiditis (HT). This research sought to examine TNF-α gene expression and assess serum concentrations of TNF-α and its soluble receptor 1 (sTNFR1) in women with HT. The study group included fifty healthy women and fifty HT women. Serum concentrations TNF-α and TNFR1 levels were evaluated using the sandwich ELISA method. The expression level of TNF-α was quantified using quantitative real-time polymerase chain reaction (qRT-PCR). Our research findings revealed a highly significant increase at p<0.001 and a strong positive correlation between TNF-α and TNFR1 (r=0.401, p= 0.004). This study showed a positive correlation between TNFR1 and Anti-Tg (r=0.298, p=0.036). The diagnostic value was significant, with an Area Under the ROC Curve (AUC) of 0.896 for TNF-α and 0.848 for TNFR1 at cut-off values of 69.465 and 32.367, respectively. Sensitivity for TNF-α and TNFR1 was 66% and 68%, respectively, while specificity was 100% (P=0.001) for both. Additionally, HT women exhibited markedly elevated expression levels of the TNF-α gene compared to HI women (P<0.046). This study demonstrates that HT disease (HTD) is strongly associated with higher levels of TNF-α and TNFR1, and increased expression of TNF-α mRNA, suggesting a link with the inflammatory process and disease progression in Iraqi women.